Program “Lansia Sabar” Berbasis Reminiscence dan Art Therapy untuk Meningkatkan Self-Compassion pada Lanjut Usia di Panti Wredha - Ni Made Rai Kistyanti; sofia retnowati (Faculty of Psychology, Universitas Gadjah Mada, 2017)
This research aimed to study the effect of reminiscence and art therapy in ‘Lansia Sabar’ Program for the enhancement of self-compassion in the Elderly in the Nursing Home. This research used a single case design method. The measurement of self-compassion was done by using self-compassion daily checklist based on components of self-compassion by Neff. Data were analyzed by visual inspection using the graphic that will show the participants’ changes between the phases. The changes that will be analyzed are the change of mean, stability level, and trend. The analysis will be supported by interview and observation data as well. The result of analysis shown 2 out of 3 participants had and an increasing mean of self-compassion in the intervention phase. The other participant had a little decreasing mean of self-compassion in the intervention phase. Overall, although there was a different result in one of the participants, the trend showed a positive response during the intervention phase.